(untitled) (Al-Qamar, 2019)
Imam Abu Baker Ahmed Ibn Husain al-Bayhaqī is considered as one of the greatest Muhaddithīn and jurists of the 4th century AH. He wrote many books on different topics. Al-Sunan al-Kubrā is one of his most famous books. This is an authentic book for Hadith and Fiqh. This is the last book of Hadith ever for any Imam with their own Sanad. Imam Bayhaqī was a Shafi’i scholar. In the sub-topics of the book, Imam Bayhaqī mentions Qurānic verses and gives them jurisprudential arguments. In this article, the same interpretive points mentioned in the chapters translated by Imam Bayhaqi have been discussed. It finds that Bayhaqī has adorned these points with comprehensive and valuable arguments.